(untitled) (Journal of Contemporary Philology, 2018)
This paper presents the results of the investigation into the syntax of anaphoric reference in narrative discourse. The main goal is to determine the principles that govern the realization of anaphoric subjects in Macedonian narratives. The analysis focuses on three types of subjects that code the protagonists in chosen narrative texts: implicit (signaled by verbal personal inflections), pronominal and nominal. The obtained distribution of each subject category is accounted for by positing a cognitive default principle according to which the form of the anaphor is governed by the cognitive status of its referent in listener/reader’s memory. However, this cognitive principle maybe superseded by the effects of other principles which cause deviations in the expected realization of anaphoric subjects. The results of the analysis confirm the main hypothesis thatthe choice of the subject form depends on the interplay of cognitive, semantic, syntactic and discourse-pragmatic principles. The effect of each principle is explained using the data from the analyzed narratives.